If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (80 + -1x) * 3x = 180 Reorder the terms for easier multiplication: 3x(80 + -1x) = 180 (80 * 3x + -1x * 3x) = 180 (240x + -3x2) = 180 Solving 240x + -3x2 = 180 Solving for variable 'x'. Reorder the terms: -180 + 240x + -3x2 = 180 + -180 Combine like terms: 180 + -180 = 0 -180 + 240x + -3x2 = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(-60 + 80x + -1x2) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-60 + 80x + -1x2)' equal to zero and attempt to solve: Simplifying -60 + 80x + -1x2 = 0 Solving -60 + 80x + -1x2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. 60 + -80x + x2 = 0 Move the constant term to the right: Add '-60' to each side of the equation. 60 + -80x + -60 + x2 = 0 + -60 Reorder the terms: 60 + -60 + -80x + x2 = 0 + -60 Combine like terms: 60 + -60 = 0 0 + -80x + x2 = 0 + -60 -80x + x2 = 0 + -60 Combine like terms: 0 + -60 = -60 -80x + x2 = -60 The x term is -80x. Take half its coefficient (-40). Square it (1600) and add it to both sides. Add '1600' to each side of the equation. -80x + 1600 + x2 = -60 + 1600 Reorder the terms: 1600 + -80x + x2 = -60 + 1600 Combine like terms: -60 + 1600 = 1540 1600 + -80x + x2 = 1540 Factor a perfect square on the left side: (x + -40)(x + -40) = 1540 Calculate the square root of the right side: 39.242833741 Break this problem into two subproblems by setting (x + -40) equal to 39.242833741 and -39.242833741.Subproblem 1
x + -40 = 39.242833741 Simplifying x + -40 = 39.242833741 Reorder the terms: -40 + x = 39.242833741 Solving -40 + x = 39.242833741 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '40' to each side of the equation. -40 + 40 + x = 39.242833741 + 40 Combine like terms: -40 + 40 = 0 0 + x = 39.242833741 + 40 x = 39.242833741 + 40 Combine like terms: 39.242833741 + 40 = 79.242833741 x = 79.242833741 Simplifying x = 79.242833741Subproblem 2
x + -40 = -39.242833741 Simplifying x + -40 = -39.242833741 Reorder the terms: -40 + x = -39.242833741 Solving -40 + x = -39.242833741 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '40' to each side of the equation. -40 + 40 + x = -39.242833741 + 40 Combine like terms: -40 + 40 = 0 0 + x = -39.242833741 + 40 x = -39.242833741 + 40 Combine like terms: -39.242833741 + 40 = 0.757166259 x = 0.757166259 Simplifying x = 0.757166259Solution
The solution to the problem is based on the solutions from the subproblems. x = {79.242833741, 0.757166259}Solution
x = {79.242833741, 0.757166259}
| 4x-1=8-2x | | 8+3q=11+2q | | -13=6-7 | | 2x-2=6x-4 | | 2x-4(x-3)=-9+5x-14 | | 3b+12-5b=22 | | 0.07-0.06(5x+4)=0.06x+0.13 | | 4x+13=-7x-30 | | 4x^2-26-14= | | 32m+54m+22=0 | | 6x-4x+20=-16 | | 2+3v=-6v-16 | | 3x+20+2(4x+4)=2x | | 26-(4x-11)=5(x+7) | | -(5z+1)=18 | | 4x+8-3x=14 | | 6x^3=5x^2 | | 3x+5.2=2-5y | | x+5=x+0 | | -13+7=-h-7+7 | | 3x-15=17-x | | 3(5y+2)-y=(2y-3) | | x=23-(-11) | | 8-3x=3x+2 | | 66=9x-13-8x+29 | | x/8+6=-12 | | 23-(-11)= | | w+(-9)=-4 | | 3x-15=3x | | 8x=6x-14 | | 2x-3=32 | | 15=5x-3(x+7) |